2015
DOI: 10.1016/j.ypmed.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in physical activity resource availability in six US regions

Abstract: We conducted an ecologic study to determine physical activity resource availability overall and by sociodemographic groups in parts of six states (CA, IL, MD, MN, NC, NY). Data on parks and recreational facilities were collected from 3 sources in 2009–2012. Three measures characterized park and recreational facility availability at the census tract level: presence of ≥1 resource, number of resources, and resource kernel density. Associations between resource availability and census tract characteristics (predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 53 publications
3
49
2
4
Order By: Relevance
“…Four additional studies not only took a similar approach but also included a buffer zone around the geographical area . Other studies employed a kernel density approach, or a buffer zone around either a population weighted centroid, a geographical centroid, a participant's home, or a random point within a geographical area . Three studies used a combination of approaches …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four additional studies not only took a similar approach but also included a buffer zone around the geographical area . Other studies employed a kernel density approach, or a buffer zone around either a population weighted centroid, a geographical centroid, a participant's home, or a random point within a geographical area . Three studies used a combination of approaches …”
Section: Resultsmentioning
confidence: 99%
“…Two studies, one conducted in Scotland and one in the United States, had U‐shaped results, with both finding fewer recreational facilities in the highest and lowest SEP areas, compared with middle SEP areas. The remaining six papers had mixed findings …”
Section: Resultsmentioning
confidence: 99%
“…In a large study including 7139 census tracts, comprising 9.5% of the 2010 US population, the availability of parks and recreational facilities was lower in predominantly minority census tracts relative to non-Hispanic white census tracts. [78] However, it may take more than small changes in the built environment to increase MVPA. The social component of choosing to use one’s neighborhood for MVPA needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should also be noted that previous research on access to recreational facility and disparities has demonstrated mixed results. For example, low-income and/or high-percent minority neighborhoods have been shown to have lesser (Moore et al, 2008; Jones et al, 2015), greater (Wen et al, 2013; Vaughan et al, 2013), or similar (Timperio et al, 2008) access to parks than their counterpart neighborhoods. Given this lack of consistency of evidence regarding disparities in access to recreational facilities, the impact of shared use agreements should be closely evaluated with particular attention paid to the role these agreements can play in addressing disparities in access.…”
Section: Discussionmentioning
confidence: 99%